Vibrio splendidus Fur regulates virulence gene expression, swarming motility, and biofilm formation, affecting its pathogenicity in Apostichopus japonicus - Shi, Yue; Liao, Changyu; Dai, Fa; Zhang, Yiwei; Li, Chenghua; Liang, Weikang (Frontiers in Veterinary Science, 2023)
Vibrio splendidus is an opportunistic pathogen that causes skin ulcer syndrome and results in huge losses to the Apostichopus japonicus breeding industry. Ferric uptake regulator (Fur) is a global transcription factor that affects varieties of virulence-related functions in pathogenic bacteria. However, the role of the V. splendidus fur (Vsfur) gene in the pathogenesis of V. splendidus remains unclear. Hence, we constructed a Vsfur knock-down mutant of the V. splendidus strain (MTVs) to investigate the role of the gene in the effect of biofilm, swarming motility, and virulence on A. japonicus. The result showed that the growth curves of the wild-type V. splendidus strain (WTVs) and MTVs were almost consistent. Compared with WTVs, the significant increases in the transcription of the virulence-related gene Vshppd mRNA were 3.54- and 7.33-fold in MTVs at the OD600 of 1.0 and 1.5, respectively. Similarly, compared with WTVs, the significant increases in the transcription of Vsm mRNA were 2.10- and 15.92-fold in MTVs at the OD600 of 1.0 and 1.5, respectively. On the contrary, the mRNA level of the flagellum assembly gene Vsflic was downregulated 0.56-fold in MTVs at the OD600 of 1.0 compared with the WTVs. MTVs caused delayed disease onset time and reduced A. japonicus mortality. The median lethal doses of WTVs and MTVs were 9.116 × 106 and 1.658 × 1011 CFU·ml−1, respectively. Compared with WTVs, the colonization abilities of MTVs to the muscle, intestine, tentacle, and coelomic fluid of A. japonicus were significantly reduced. Correspondingly, the swarming motility and biofilm formation in normal and iron-replete conditions were remarkably decreased compared with those of WTVs. Overall, these results demonstrate that Vsfur contributes to the pathogenesis of V. splendidus by regulating virulence-related gene expression and affecting its swarming and biofilm formation abilities.